English Teaching Media in Class Implementing Curriculum 2013 - Putra Mahardhika (Bandar Lampung University (UBL), 2014)
As new curriculum proposed by government, Curriculum 2013 is intended to give beneficial impact to learners in Indonesia. In order to give beneficial impact, Curriculum 2013 was proposed by bringing new thoughts. From those thoughts, there is changing concept about teaching media. That is concept about changing single media to multimedia. Media is then considered as the important thing in class. One of the subjects which need media is English. It is because English has skills such as listening, speaking, reading and writing. Consequently, it is appropriate to use various media in class. This study tries to investigate the use of English teaching media in class which implements Curriculum 2013. This study then observed class of English implementing Curriculum 2013. The data were also taken by interviewing the teacher who teaches English in the class implementing Curriculum 2013. At the end, this study may be needed by those having attention on education and curriculum.